(untitled) (Proceedings of International Conference on Educational Discoveries and Humanities, 2024)
Road traffic accidents (RTAs) are one of the leading causes of injury and mortality. The effectiveness of treatment for road accident victims often depends on the mechanism of injury factors, such as the type of collision, the direction of impact, and the speed of the vehicle. Studying these factors helps optimize treatment protocols and improve patient outcomes.